The impact of Russia’s cooperation with the G7 countries in the sphere of trade in goods on the national economy of Russia - A. G. Glebova; A. A. Gilyadova; E. A. Martakova (Вестник университета)
The subject of the study is the foreign trade turnover between Russia and the G7 countries (USA, Canada, France, Germany, Italy, Japan, Great Britain), in particular, its structure. The purpose of the work is to identify the degree of influence of Russia’s cooperation with the countries considered in the work in the field of trade in goods on the national economy of Russia. The theoretical and methodological basis and information base of the study are the works of Russian and foreign authors devoted to the issues of interaction between Russia and the G7 countries. While writing this article the authors also referred to official Russian sources, in particular, to the data provided by the Federal Customs Service of Russia, the Federal State Statistics Service (Rosstat), and the Ministry of Finance of the Russian Federation. It is concluded that Russia’s cooperation with the G7 countries in the sphere of foreign trade is generally effective for Russia. However, it should be noted that the Russian Federation is actively implementing an export-oriented policy, the main products of which are oil products, which undoubtedly contributes to the increase in the rate of economic development, the inflow of foreign capital and the increase in gross domestic product. But due to the imposed sanctions, as well as dependence of the Russian Federation on oil and gas revenues, it is necessary to direct the vector of development to other industries, pay special attention to the development of domestic products and diversify the economy. The results obtained in this paper can be used for forecasting the economic position of the country in the global arena, analyzing the further interaction of the Russian Federation with its key trading partners, and assessing the feasibility of an effective partnership.